2017
DOI: 10.1108/bfj-11-2016-0557
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences towards healthier reformulation of a range of processed meat products

Abstract: Purpose-In response to increasing public health concerns about processed meat consumption, many innovations in meat technology focus on health-oriented product reformulations. Processed meat is not a homogeneous food category. The purpose of this paper is to explore consumer perception of the "healthier" reformulation of different processed meat products using two approaches: salt and fat reduction; and enrichment with healthy ingredients. Design/methodology/approach-Seven focus group interviews were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 50 publications
(75 reference statements)
1
35
0
1
Order By: Relevance
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 clearly shows that numerous factors influence consumers when assessing the healthiness of a product. In our literature analysis, we categorized these factors as follows: Communicated information [ 26 , 27 , 34 , 35 , 37 , 47 , 60 , 62 , 65 , 73 , 74 , 77 ]; The shape and colour of the product packaging [ 23 , 25 , 28 , 32 , 33 , 43 , 61 , 66 , 70 , 71 ]; The ingredients of the product [ 24 , 29 , 39 , 40 , 49 , 57 , 64 , 76 ]; Product category [ 54 , 61 , 69 , 70 , 75 , 78 ]; Organic origin of the product [ 5 , 31 , 42 , 45 , 46 , 48 , 51 , 55 , 68 ]...…”
Section: Resultsmentioning
confidence: 99%
“…Health-oriented reformulations of processed meat are promising in terms of addressing increasing public health concerns regarding this food category; however, consumer acceptance cannot be taken for granted. For instance, a qualitative study has shown that different processed meat products are not equally perceived by consumers as suitable for healthier reformulations (Shan et al, 2017b). In relation to reformulation strategies, consumers are generally positive towards salt and fat reduction, and the replacement of nitrite with non-chemical preservatives;…”
Section: Introductionmentioning
confidence: 99%
“…However, some categories of meat products are considered as unhealthy by Brazilian consumers, due to the amount of fat and salt. Some researchers have demonstrated meat products with new health attributes (Baba, Kallas, Costa‐Font, Gil, & Realini, ; Decker & Park, ; Shan et al, ; Vogel, Pazuch, Sarmento, Back, & Secco, ; Weiss, Gibis, Schuh, & Salmine, ).…”
Section: Introductionmentioning
confidence: 99%